PRE-SERVICE SCIENCE TEACHERS’ ABILITY IN RECONSTRUCTING LOCAL COMMUNITY’S INDIGENOUS KNOWLEDGE - Parmin, Parmin; Sajidan, Sajidan (Jurnal Pengajaran MIPA, 2017)
Sociocultural aspect is considered as important consideration in pre-service science teachers’ educational program. The objective of the study was to improve the ability of pre-service science teachers in reconstructing local community indigenous knowledge. Subjects were 87 pre-service science teachers from three universities in Central and East Java with Dieng Plateau’ community indigenous knowledge in breastfeeding as knowledge that they have to reconstruct. Results suggested that pre-service science teachers were able to reconstruct the indigenous knowledge well. Implication to pre-service science teacher’s educational program is discussed.